2020
DOI: 10.1101/2020.04.28.066035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atypical meiosis can be adaptive in outcrossedS. pombedue towtfmeiotic drivers

Abstract: Killer meiotic drivers are genetic parasites that destroy ‘sibling’ gametes lacking the driver allele. The fitness costs of drive can lead to selection of unlinked suppressors. This suppression could involve evolutionary tradeoffs that compromise gametogenesis and contribute to infertility. Schizosaccharomyces pombe, an organism containing numerous gamete-killing wtf drivers, offers a tractable system to test this hypothesis. Here, we demonstrate that in scenarios analogous to outcrossing, wtf drivers generate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…We then introduced the plasmids into S. cerevisiae and analyzed the phenotypes of the resulting strains. We found that induction of each of the putative Wtf poison proteins, except S. In S. pombe, the Wtf antidote protein encoded by one wtf gene generally cannot neutralize the Wtf poison protein encoded by a different wtf gene (Bravo Núñez et al, 2020b, 2018aHu et al, 2017). Instead, a high level of sequence identity appears to be required for a Wtf antidote protein to co-assemble with and neutralize a Wtf poison protein (Nuckolls et al, 2020).…”
Section: Wtf Genes Show Evolutionary Signatures Consistent With a His...mentioning
confidence: 83%
See 4 more Smart Citations
“…We then introduced the plasmids into S. cerevisiae and analyzed the phenotypes of the resulting strains. We found that induction of each of the putative Wtf poison proteins, except S. In S. pombe, the Wtf antidote protein encoded by one wtf gene generally cannot neutralize the Wtf poison protein encoded by a different wtf gene (Bravo Núñez et al, 2020b, 2018aHu et al, 2017). Instead, a high level of sequence identity appears to be required for a Wtf antidote protein to co-assemble with and neutralize a Wtf poison protein (Nuckolls et al, 2020).…”
Section: Wtf Genes Show Evolutionary Signatures Consistent With a His...mentioning
confidence: 83%
“…We first looked for similarities in overall gene structure between the S. pombe wtf genes and the candidate wtf genes in S. octosporus , S. osmophilus and S. cryophilus . The wtf genes of S. pombe have been classified into three broad categories: predicted meiotic drivers (4-14 per isolate), predicted suppressors of drive that encode only antidote proteins (9-17 per isolate) and genes of unknown function (4 in each isolate) (Bravo Núñez et al, 2020b, 2018a; Eickbush et al, 2019; Hu et al, 2017; Nuckolls et al, 2017). We found that the overall gene structure of the candidate wtf genes in all three species was similar to that of the 5-exon wtf drivers and 5-exon wtf suppressors in S. pombe (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations